HAMBATAN DALAM PENANGANAN KASUS KEKERASAN DALAM RUMAH TANGGA - Yuliandari, Erna (PKn Progresif, 2006)
In Indonesia , the violence case in household is increasing. As we Know women are weak creatures, so they can easily be an object or victims the violence in hose hold. The number of cases caught is not as many as the one actually occurs, because the case is still considered as the household affair that does not deserve to be known by public. Patriarchy culture becomes one of obstacles for the victim, most of them are women, to report violence they experience to the police due to a great number of law do not help the women remaining, and the law apparatus not sensitive to the gender in handling violence case in household. Because of this conditions the law enforcement process in case of violence household didn?t successfully especially in giving protection to women in the violence case in household